Biological Control of Chili Damping-Off Disease, Caused by Pythium myriotylum - Hyder, Sajjad; Gondal, Amjad Shahzad; Rizvi, Zarrin Fatima; Atiq, Rashida; Haider, Muhammad Irtaza Sajjad; Fatima, Nida; Inam-ul-Haq, Muhammad (Frontiers in Microbiology, 2021)
Pythium myriotylum is a notorious soil-borne oomycete causes post-emergence damping off in chili pepper. Of various disease management strategies, utilization of plant growth promoting rhizobacteria (PGPR) in disease suppression and plant growth promotion is eye catching strategy. The present study was performed to isolate and characterize PGPR indigenous to chili rhizosphere in Pakistan, and to test their potential to suppress damping off and plant growth promotion in chili. Out of total 28 antagonists, 8 bacterial isolates (4a2, JHL-8, JHL-12, 1C2, RH-24, 1D, 5C and RH-87) significantly suppressed the colony growth of P. myriotylum in dual culture experiment. All the tested bacterial isolates were characterized for biochemical attributes, and 16S rRNA sequence based phylogenetic analysis identified these isolates as Flavobacterium spp., Bacillus megaterium, Pseudomonas putida, Bacillus cereus and Pseudomonas libanensis. All the tested bacterial isolates showed positive test results for ammonia production, starch hydrolase (except 4a2), and hydrogen cyanide production (except 4a2 and 1D). All the tested antagonists produced indole-3-acetic acid (13.4-39.0 μg mL−1), solubilized inorganic phosphate (75–103 μg mL-1) and produced siderophores (17.1–23.7 %) in vitro. All the tested bacterial isolates showed varied level of susceptibility and resistance response against different antibiotics and all these bacterial isolates were found non-pathogenic to chill seeds and notably enhanced percentage seed germination, plumule, redical length and vigor index over un-inoculated control. Additionally, under pathogen pressure, bacterization increased the defense related enzymes such as Peroxidase (PO), polyphenol oxidase (PPO) and phenylalanine ammonia-lyase (PAL) activates. Moreover, chili seeds treatment with these bacterial isolates significantly suppressed damping-off caused by P. myriotylum, and improved PGP traits as compared to control. In addition, a positive correlation was noticed between shoot, root length and dry shoot and root weigh and a negative correlation was seen between dry shoot, root weight and seedling percentage mortality. These results showed that native PGPR possess multiple traits beneficial to the chili plants and can be used to develop eco-friendly and effective seed treatment formulation as an alternative to synthetic chemical fungicides.